O-016 Outcomes after endovascular mechanical thrombectomy for low national institutes of health stroke scale (NIHSS): a multicenter study. (23rd July 2022) - Abecassis, I; Almallouhi, E; Chalhoub, R; Kassab, S; Bass, E; Ding, D; Maier, I; Psychogios, M; Liman, J; Alawieh, A; Wolfe, S; Arthur, A; et al.
Abstract : Background: The role of endovascular mechanical thrombectomy (MT) in patients presenting with 'minor' stroke is uncertain. There are also variable definitions reported for 'minor' stroke based on the National Institutes of Health Stroke Scale (NIHSS) Objective: To compare various cohorts of 'low' and 'high' NIHSS using cutoff threshold values for NIHSS of 5, 6, 7, or 8. We also aimed to compare outcomes after MT for ischemic stroke patients presenting with NIHSS < 5 versus >5 and identify predictors of a favorable outcome, mortality, and symptomatic intracranial hemorrhage (ICH). Methods: We retrospectively analyzed a prospectively maintained, international, multicenter database. Results: The study cohort comprised a total of 7, 568 patients from 29 centers. NIHSS was low (< 5) in 604 patients (8%), and >5 in 6, 964 (92%). Patients with low NIHSS were younger (67 ± 14.8 versus 69.6 ± 14.7 years, p <0.001), more likely to have diabetes (31.5% versus 26.9%, p = 0.016), and less likely to have atrial fibrillation (26.6% versus 37.6%, p <0.001) compared to those with higher NIHSS. Radiographic outcomes (TICI > 2B 84.6% and 84.3%, p = 0.412) and complication rates (8.1% and 7.2%, p = 0.463) were similar between the low and high NIHSS groups, respectively. Length of stay (LOS) was shorter in the low NIHSS group compared to the high (9 ± 7.5 vs. 10.9 ± 11.3 days, p<0.001). Clinical outcomes at every follow up interval, including NIHSS at 24 hours and discharge, and mRS at discharge and 90 days, were better in the low NIHSS group. The delta and percentage change NIHSS values (comparing admission to 24 hour values) were actually negative for the low NIHSS group, with patients experiencing clinical worsening in NIHSS in the low group (-2.02 ± 6.95 or -76 ± 269%) compared to a improvement in the high NIHSS group (+4.45 ± 8.05 or 24 ± 58%). Subsequent stratification of the low NIHSS group into 'ultra-low' (i.e. NIHSS 1–3) and low (i.e. NIHSS 4–5) groups revealed that this increase in NIHSS at 24 hours relative to admission was only observed in the ultra-low group. Mortality was lower in the low NIHSS group (10.4% versus 24.5%, p<0.001). Conclusions: MT is an effective and safe treatment for appropriately selected ischemic stroke patients presenting with low NIHSS. Diabetes and prior stroke are predictors of functional dependence at 90 days, and prior stroke is also associated with mortality, suggesting that MT should be offered judiciously to patients with these risk factors. Our findings signal the need for a randomized trial comparing MT versus medical management for LVO patients with low NIHSS. Disclosures: I. Abecassis: 2; C; IschemaView (Rapid), Remedy Robotics. E. Almallouhi: None. R. Chalhoub: None. S. Kassab: None. E. Bass: None. D. Ding: None. I. Maier: None. M. Psychogios: None. J. Liman: None. A. Alawieh: None. S. Wolfe: None. A. Arthur: 1; C; Balt, Medtronic, Microvention, Penumbra, Siemens. 2; C; Balt, Johnson and Johnson, Microvention, Medtronic, Penumbra, Scientia, Siemens, Stryker. 4; C; Azimuth, Bendit, Cerebrotech, Endostream, Magneto, Mentice, Neurogami, Serenity, Synchron, Triad medical, Vastrax, VizAI. P. Kan: None. J. Kim: None. R. De Leacy: 1; C; Hypervenetion, Siemens. 2; C; Stryker, Medical Metrics, Proxima, Cerenovus, Asahi Intec, Imperative Care. 4; C; Spartan Micro, Vastrax, QApel, Synchron, Endostream. J. Osbun: 2; C; Medtronic, Terumo, Microvention, In Neuro Co. P. Jabbour: None. J. Grossbereg: 1; C; Georgia Research Alliance, Emory Medical Care Foundation, Emory Neurosurgery Catalyst. 2; C; Cognition. M. Park: None. J. Mascitelli: 2; C; Stryker. M. Levitt: None. A. Polifka: None. S. Yoshimura: None. C. Matouk: None. R. Williamson: None. B. Gory: None. M. Mokin: None. I. Fragata: None. D. Romano: 2; C; Microvention, Balt, Penumbra. V. Saini: None. M. Moss: None. D. Behme: None. K. Limaye: None. A. Spiotta: 1; C; Penumbra, Stryker, IschemaView/Rapid AI. 2; C; Penumbra, Stryker, Cerenovus, Terumo, IschemaView Inc, RAPID AI. R. Starke: 1; C; NREF, Joe Niekro Foundation, Brain Aneurysm Foundation, Bee Foundation, National Institute of Health (R01NS111119-01A1) and (UL1TR002736, KL2TR002737), Medtronic. 2; C; Medtronic, Penumbra, Abbott, InNeuroCo, Cerenovus.